Peran Guru Ekonomi dalam Penggunaan Media Visual untuk Meningkatkan Minat Belajar Siswa Kelas X SMAN 1 Lewolema - Maria Enjelica Colorosa; Reinaldis Masi; Maria Fatima Bongi Beribe (Jurnal Pendidikan dan Sastra Inggris, 2025)
Digital transformation in education demands a fundamental shift in the role of teachers from traditional instructors to modern learning facilitators. This research explores the multidimensional role of economics teachers in optimizing visual learning media to arouse students' interest in learning in the digital era. Using a descriptive qualitative approach, this study involved one economics teacher and 23 class X students at SMAN 1 Lewolema through observation, interviews, and documentation. The findings reveal that teachers successfully operationalize multidimensional roles as learning designers, interactive facilitators, motivators, and educational innovators through strategies that integrate visual media with contextual and interactive approaches. Visual learning media has proven to be effective in transforming students' learning experiences to be more holistic, covering three main dimensions: affective, cognitive, and contive. Indicators include increased feelings of pleasure in the material, active involvement in the learning process, high interest in visual content, and improved focus and concentration during learning activities. However, the implementation of the use of visual media is inseparable from complex challenges. The main obstacles found include the limitations of school technology infrastructure, the digital competency gap that is still experienced by some teachers, and the diversity of students' psychological characteristics that affect their response to visual media. In addition, the lack of technical support and a specific budget for media development is also a factor inhibiting the sustainability of visual-based learning innovations. To overcome this, progressive education policy support, continuous training for teachers, and the development of adaptive and contextual visual media according to student needs are needed.